The Influence of Industrial Work Practices on Student Work Readiness at Smk Negeri 1 Cilaku - Yola Ananda Putri; Odih Supratman; Dedi Purwanto; Wei-Te Liu (Jurnal Pendidikan Teknik Sipil, 2023)
Background:  Internship is one of the programs implemented to connect vocational schools with the working world. Working readiness is the ability to carry out or complete in accordance with the predetermined conditions. In this case, this research was carried out to: (1) know the description of internships carried out by vocational school students; (2) know the description of the working readiness of students after participating in internship activities; and (3) know the effect of internship on working readiness of final year students in building information modelling design at SMKN 1 Cilaku.Methods: There are two variables studied in this research, including industrial work practices (X) and work readiness (Y). The research method used in this research is a quantitative method, while in order to answer the problem, the authors used a trend test and simple linear regression analysis. Furthermore, the data collection was done using questionnaires with a Likert scale.Results: Based on the findings and discussion, (1) internship outcomes have a tendency of quite decent with an average score of 79%, (2) working readiness outcomes have a tendency of quite decent with an average score of 79%, and (3) internship on working readiness have a positive and significant influence and the influence of internship on working readiness by 42%.Conclusion: It can be concluded that the implementation of industrial work practices in Cilaku State Vocational School 1 students has a tendency to be in the sufficient category, class student work readiness is in the sufficient category, and industrial work practices have a positive influence on student work readiness. In other words, students are quite ready to enter the world of work.